(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
According to the Seoul Metro, the number of civil complaints regarding pregnant women’s caring seat in 2018 was approximately 27,600 cases. Pregnant women who are the beneficiaries of this system cannot use such seat properly, creating a negative view in the society. In this study, user information is collected using database and the subway information such as arrival time is received through Open API for ‘Pink Light’ which has not been used properly after its introduction. Such system is supplemented using RFID or QR Code and ultrasonic sensor, and the real-time seating chart for pregnant women and general passengers in the subway train is introduced using a simple application for solving the problem. In the end, this study intends to design and implement a system that can promote the convenience for both pregnant women and general passengers by ensuring pregnant women to be able to use pregnant women’s caring seats freely without having a regard for other passengers’ feelings and by increasing the number of general passenger seats.